Demographic performance of European tree species at their hot and cold climatic edges - Kunstler, G; Guyennon, A; Ratcliffe, S; Rueger, N; Ruiz-Benito, P; Childs, DZ; Dahlgren, J; Lehtonen, A; Thuiller, W; Wirth, C; Zavala, MA; Salguero-Gomez, R (Wiley, 2020)
Species range limits are thought to result from a decline in demographic performance at range edges. However, recent studies reporting contradictory patterns in species demographic performance at their edges cast doubt on our ability to predict climate change demographic impacts. To understand these inconsistent demographic responses, we need to shift the focus from geographic to climatic edges and analyse how species responses vary with climatic constraints at the edge and species' ecological strategy. Here we parameterised integral projection models with climate and competition effects for 27 tree species using forest inventory data from over 90,000 plots across Europe. Our models estimate size-dependent climatic responses and evaluate their effects on two life trajectory metrics: life span and passage time—the time to grow to a large size. Then we predicted growth, survival, life span and passage time at the hot and dry or cold and wet edges and compared them to their values at the species climatic centre to derive indices of demographic response at the edge. Using these indices, we investigated whether differences in species demographic response between hot and cold edges could be explained by their position along the climate gradient and functional traits related to their climate stress tolerance. We found that at cold and wet edges of European tree species, growth and passage time were constrained, whereas at their hot and dry edges, survival and life span were constrained. Demographic constraints at the edge were stronger for species occurring in extreme conditions, that is, in hot edges of hot-distributed species and cold edges of cold-distributed species. Species leaf nitrogen content was strongly linked to their demographic responses at the edge. In contrast, we found only weak links with wood density, leaf size and xylem vulnerability to embolism. Synthesis. Our study presents a more complicated picture than previously thought with demographic responses that differ between hot and cold edges. Predictions of climate change impacts should be refined to include edge and species characteristics.